Abuso Infantil: significados e condutas de dentistas da Estratégia Saúde da Família de Belo Horizonte - um estudo qualitativo - Laís Soares Nunes (2020)
Child abuse is a serious public health problem. Dentists are in a strategic position to identify and report child abuse. However, studies point to a high prevalence of nonnotification behavior by these professionals. In addition, dentists are often associated with difficulties in identifying and reporting cases of child abuse among their patients. The literature lacks studies that work on these factors in depth. Given the above, some questions are raised: Why are dentists frequently associated with high prevalence of non-notification behavior? How do they perceive child abuse in the context and daily work of primary health care? What are the conceptions of child abuse built by dentists? How do the factors associated with the identification and reporting of child abuse influence dentists' approach of cases? These questions supported the construction of this study. The aim of this study was to develop a substantive theoretical model that would allow understanding how these factors are related to the identification and reporting of child abuse by dentists of the Family Health Strategy (FHS) in Belo Horizonte in their daily work. A qualitative study was carried out, following the Grounded Theory methodological framework, in the theoretical light of Symbolic Interactionism. The sample selection was intentional and characterized by theoretical sampling. Data collection was performed through semi-structured individual interviews and the criterion for finalizing the collection was saturation. We interviewed 10 dentists linked to the FHS. The study resulted in the construction of a theory about the Child Abuse Approach by FHS Dentists, which consists of 3 categories. The first category called Conception of Abuse, presents the set of meanings and concepts that define what child abuse is for professionals. The second, called Conception on the Notification and Protection System for Children and Adolescents, presents concepts and meanings attributed to the notification of child abuse and its processes. The third category, called Conducts, presents the elements that involve the attitudes and behaviors taken by dentists in the face of suspected or confirmed cases of child abuse. Dentists' views on the topic are important and strongly influence their approach to child abuse. The concepts presented are flawed because there is mainly a lack of technical training on the subject. In addition, the child abuse approach is influenced and involves from individual issues of professionals, to social, cultural and organizational issues in the health system. This study presents important contributions for dentists and the FHS. Its results can be used to support the construction and development of intervention studies on the topic.